Experimental and Numerical Study on Ultimate Shear Load Carrying Capacity of Corroded RC Beams - Zhanzhan Tang; Zhixiang He; Zheng Chen; Lingkun Chen; Hanyang Xue; Hanqing Zhuge (Advances in Civil Engineering)
For an RC beam, the strength of steel rebar, the bonding strength between the concrete and reinforcement, and the bite action between the aggregates will deteriorate significantly due to corrosion. In the present study, 10 RC beams were designed to study the impact of corrosion on the shear bearing capacity. The mechanism of corrosion for stirrups and longitudinal bars and their effects were analyzed. Based on the existing experimental data, the correlation between the stirrup corrosion factor and the cross section loss rate was obtained. An effective prediction formula on the shear bearing capacity of the corroded RC beams was proposed and validated by the experimental results. Moreover, a numerical analysis approach based on the FE technique was proposed for the prediction of the shear strength. The results show that corrosion of the reinforcements could reduce the shear strength of the RC beams. The corrosion of stirrups can be numerically simulated by the reduction of the cross section. The formulae in the literature are conservative and the predictions are very dispersed, while the predictions by the proposed formula agree very well with the experiment results.